Wrist-Worn Electrodermal Activity as a Novel Neurophysiological Biomarker of Autonomic Symptoms in Spatial Disorientation - Tamura, Atsushi; Iwamoto, Tetsuya; Ozaki, Hirokazu; Kimura, Mikihiko; Tsujimoto, Yukiko; Wada, Yoshiro (Frontiers in Neurology, 2018)
Background: Spatial disorientation is one of the most frequent causes of aircraft accidents, and is thus a major problem affecting air safety. Although a number of studies have examined spatial disorientation, the precise physiological changes occurring as a direct result of spatial disorientation and motion sickness remain unclear. The present study sought to investigate electrodermal activity (EDA) and subjective autonomic symptoms during spatial disorientation training, and to develop an indicator of physiological changes for pilot candidates. Methods: In the current study, we investigated changes in EDA measured using a wrist-worn device, and subjective autonomic nervous system symptoms during spatial disorientation training for pilot candidates. We then used the Graybiel diagnostic criteria to develop a novel physiological biomarker. Results: We found that maximum EDA change and peak amplitude were significantly increased in participants with a Graybiel score of ≥ 3 points compared with those who scored < 2 points. Furthermore, for symptoms of cold sweating and saliva secretion (from the seven Graybiel diagnostic criteria), the maximum EDA change in participants with scores ≥ 1 point was significantly higher than that of participants scoring 0 points. Conclusion: Our results indicate that EDA data measured with a wrist-worn device might be useful for objective evaluation of the severity of spatial disorientation and motion sickness.